2022
DOI: 10.3389/fmed.2022.987202
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning reduces frontal and hippocampal neuronal dysfunction in a murine model of ventilator-induced lung injury

Abstract: Prone positioning is an established treatment for severe acute lung injury conditions. Neuronal dysfunction frequently occurs with mechanical ventilation-induced acute lung injury (VILI) and clinically manifests as delirium. We previously reported a pathological role for systemic interleukin 6 (IL-6) in mediating neuronal injury. However, currently no studies have investigated the relationship between prone or supine positioning and IL-6 mediated neuronal dysfunction. Here, we hypothesize that prone positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Apart from this, a systematic review of ten trials concluded that prone positioning reduces the risk of pneumonia and improves oxygenation in mechanically ventilated patients ( Sud et al, 2008 ). Furthermore, in a C57BL/6J mice VILI model, Sparrow et al initially reported that prone positioning diminished inflammatory cytokines and neuronal damage in the frontal brain and hippocampus via the IL-6 trans-signaling pathway, which might assist with CI due to VILI ( Sparrow et al, 2022 ). These suggest that the therapeutic effect of postural therapy for VILI itself and the resulting cognitive impairment has also been validated.…”
Section: Prevention and Treatment Strategiesmentioning
confidence: 99%
“…Apart from this, a systematic review of ten trials concluded that prone positioning reduces the risk of pneumonia and improves oxygenation in mechanically ventilated patients ( Sud et al, 2008 ). Furthermore, in a C57BL/6J mice VILI model, Sparrow et al initially reported that prone positioning diminished inflammatory cytokines and neuronal damage in the frontal brain and hippocampus via the IL-6 trans-signaling pathway, which might assist with CI due to VILI ( Sparrow et al, 2022 ). These suggest that the therapeutic effect of postural therapy for VILI itself and the resulting cognitive impairment has also been validated.…”
Section: Prevention and Treatment Strategiesmentioning
confidence: 99%